Towards a Peruvian Critical Deontology: The Reflection of Antonio Cornejo Polar and Raúl Bueno Chávez on the Work of Literary Criticism in Peru - Torres-Astocóndor, Carlos (2022)
This paper aims to explore and argue that in Peruvian literary criticism there is a tradition of reflection on its function. To this end, the critical work of Antonio Cornejo Polar and Raúl Bueno Chávez will be analyzed on the basis of “critical deontology”, a category that tracks the duties and principles that literary critics maintain are necessary when performing their function. Therefore, this paper reviews Peruvian literary criticism, and in particular the works of Antonio Cornejo Polar and Raúl Bueno Chávez, from a deontological valuation. There are three commonalities between the authors proposals: first, to consider the social situation as an essential element in the critical activity, since Peru presents a multicultural and multilingual reality; second, to dominate disciplines close to literature, such as sociology, history, anthropology, philosophy, linguistics, etc., in order to broaden the interpretative dimension of literary criticism. Finally, the authors recognize that critical activity is also a political and ideological action that takes shape through dimensions that go beyond their personal experience, since it includes training and professional relationships that delimit the spaces for future research.